Hybrid Simulation of a Frame Equipped with MR Damper by Utilizing Least Square Support Vector Machine - A H. Sharghi; R. Karami Mohammadi; M. Farrokh (Numerical Methods in Civil Engineering)
In hybrid simulation, the structure is divided into numerical and physical substructures to achieve more accurate responses in comparison to a full computational analysis. As a consequence of the lack of test facilities and actuators, and the budget limitation, only a few substructures can be modeled experimentally, whereas the others have to be modeled numerically. In this paper, a new hybrid simulation has been introduced utilizing Least Square Support Vector Machine (LS-SVM) instead of physical substructures. With the concept of overcoming the hybrid simulation constraints, the LS-SVM is utilized as an alternative to the rate-dependent physical substructure. A set of reference data is extracted from appropriate test (neumerical test) as the input-output data for training LS-SVM. Subsequently, the trained LS-SVM performs the role of experimental substructures in the proposed hybrid simulation. One-story steel frame equipped with Magneto-Rheological (MR) dampers is analyzed to examine the ability of LS-SVM model. The proposed hybrid simulation verified by some numerical examples and  results demonstrate the capability and accuracy of  this new hybrid simulation.